Sensors for Ultrasonic NDT in Harsh Environments - Sinclair, Anthony N. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In this Special Issue of Sensors, seven peer-reviewed manuscripts appear on the topic of ultrasonic transducer design and operation in harsh environments: elevated temperature, high gamma and neutron radiation fields, or the presence of aggressive chemicals. Motivations for these research and development projects are strongly focused on nuclear power plant inspections (particularly liquid-sodium cooled reactors), and nondestructive testing of high-temperature piping installations. It is anticipated that extensive use of permanently mounted robust transducers for in-service monitoring of petrochemical plants and power generations stations; quality control in manufacturing plants; and primary and secondary process monitoring in the fabrication of engineering materials will soon be made.